Scotland's referendum and the media : national and international perspectives - Blain, Neil, 1951-; Hutchison, David, 1944 September 24-; Hassan, Gerry (Edinburgh University Press, 2016)
This collection of essays explores how the 2014 Scottish referendum was presented in the media not only in Scotland but elsewhere in the United Kingdom, in Europe and beyond.